Réponses

2013-05-19T15:29:03+02:00

48)   4x + 5= 3x - 2

            4x -3x = -2 -5

                   x  = - 7

 

5x - 3 = 7x +9

5x - 7x = 9 +3

- 2x = 12

x = -12/2 = -6

 

7x - 6 = 3x +7

7x -3x = 7 +6

4x = 13

x= 13/4

 

12x - 7 =15x +2

12x - 15x = 2+7

- 3x = 9

x= -9/3 = -3

 

49)   7x -8 = 3x +6

         7x -3x = 6 +8

          4x = 14

           x = 14/4 = 7/2 .

 

3x -2 = 5x +3

3x - 5x = 3+2

- 2x = 5

x = -5/2

 

3x-5 = 8x-11

3x -8x = -11 +5

-5x = -6

x = 6/5

 

7x+7 =9x -3

7x -9x = -3 -7

-2x = -10

x = 10/2 = 5